Immobilization of Lipase from Rhizopus delemar on Polyethylene Membrane - Retno Indrati; Djagal W Marseno; Yoshiyuki Ohta (Indonesian Association of Food Technologists, 1999)
Rhizopus delemar lipase was immobilized by physical adsorption onto polyethylene membranes. The influence of membrane pore size and thickness on enzyme activity was studied. The immobilization efficiency was higher for the thicker membrane than thin one, this related to the large excess of area that the enzyme can occupy. The immobilization efficiency was also affected by enzyme loading, in which suppression was occurred at high enzyme loading. At the initial rate of hydrolysis reaction, the amount of enzyme bound, concentration of substrate, and membrane's thickness as related to the limitation of the substrate transfer affected the production of fatty acid. The thin polyethylene membrane was the best support since the enzyme immobilized on this support was stable during storage and possessed higher degree of hydrolysis and ability for subsequent reuses. Both membranes were regenerable by washing for fresh enzyme immobilization.